Halal Tourism in Lombok Island: Potentials, Challenges, and the Role of Islamic Education - Mohamad Iwan Fitriani; Nazar Naamy (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2019)
Although Lombok of West Nusa Tenggara has gained an excellent international reputation for its halal tourism (2015-2018), tourism in the region is not without obstacles. Several elements of the Sasak-Lombok community, for instance, still refuse the concept of halal tourism because it is likely to cause harm to conventional tourism. This article will examine potentials, challenges, and the role of Islamic education in halal tourism in Lombok. It employs a descriptive-qualitative approach, where data collection is obtained from focus group discussions, in-depth interviews, document analysis, and media reporting. Meanwhile, data validity testing is carried out with the triangulation technique. After a profound analysis, this research found that: (1) the potentials for halal tourism in Lombok are made of its natural beauty, cultural distinctiveness, and tradition of the local community predominated by Muslims; (2) the challenges of halal tourism in Lombok include two things: a) conceptual challenges that deal with the absence of terms representing the desires of all parties, and b) practical problems that deal with economic, environmental, social, and cultural matters; (3) Islamic education—as a value, activity, or institution—plays a vital role in disseminating representative concepts for halal tourism acceptable to all parties, i.e. the local community, tourism actors, and government. This acceptance is one of the keys to the successful development of halal tourism in Lombok.